Ways of being in teaching : conversations and reflections - Wiebe, Sean, 1969-; Lyle, Ellyn; Wright, Peter R. (College teacher); Dark, Kimberly; McLarnon, Mitchell; Day, Liz (Sense Publishers, 2017)
As teachers, we share experiences with one another. It is a way to make sense of our teaching lives and teaching selves. Ways of Being in Teaching is that kind of sharing; it is a scholarly conversation that will appeal to teachers who are tired of the tips and tricks, and want to talk more deeply about how to flourish in this profession. Most of us know ways to strengthen and sustain self, soul, heart, identity, and how these key touchstones also strengthen teaching. This book recognizes that who we are, where we are, and why, is as much a social process as a personal one. Attending to life purpose is a way of attending to teaching. Chapters in this text are insightfully forthright, challenging us to undertake the rigourous work of discovering who we are as human beings and how this impacts who we are with our students. Canadian curriculum scholar Cynthia Chambers asks us to listen for what keeps us awake at night, and with Ways of Being in Teaching we bring what we have heard into the daylight, into the conversation. "This collection of reflections and conversations does more than provide provocative reading for the reflective teacher. It invites practitioners to find their own place at the table of sharing and to welcome the stories that will certainly come as a result of engaging with this community of life writers."--Carmen Schlamb, Professor, Seneca College